Pengaruh Jumlah Penduduk, Jumlah Kunjungan Wisatawan Nusantara (Wisnus), dan Pertumbuhan Ekonomi (PE) Terhadap Pendapatan Asli Daerah (PAD) di Provinsi Sumatera Barat - Yanti, Suci Putri; Kurniawati, Tri (Universitas Negeri Padang, 2024)
This research with the title of the influence of population, wisnus, and PE on PAD in West Sumatra Province was conducted with the aim of seeing how the impact of the three independent variables on the dependent variable both simultaneously and partially. This research was conducted in the 2018-2022 time period in the district / city in West Sumatra Province using the panel data regression analysis method. With variables of Total Population (X1), Number of Tourist Visits (Wisnus) (X2), and Economic Growth (PE) (X3), and Regional Original Revenue (PAD) (Y). The results of panel data regression analysis show that Population, Number of Tourist Visits (Wisnus), and Economic Growth (PE) jointly affect Regional Original Revenue (PAD) in West Sumatra Province, while partially Population has a positive and significant effect on PAD in West Sumatra Province. The variable wisnus has a positive and insignificant effect on PAD in West Sumatra Province. Furthermore, the PE variable has a positive and significant correlation on PAD in West Sumatra Province.